The diffusion of managerial practices in performance perspective: a review of transfer models in health systems - Ndayishimiye, Richard; Niyondiko, Dominique; Bigawa, Abel Bazira (International Journal Of Community Medicine And Public Health, 2020)
Managerial practices are widely held to be a vital component of efficient organizations, especially in public services where they are being transferred for the last decades. From a performance perspective, health systems of many developing countries were inspired by multiple existing transfer models to introduce these managerial practices according to new public management orientations. However, the used transfer models seem to ignore some action mechanisms as important aspects of this process. This paper aims at presenting the state of the art in transfer models of managerial practices in health systems. Ten main transfer models related to the research theme were identified. We organized the review around a number of questions that are raised explicitly or implicitly by the literature and observation on transfer models. The full implication became clear after using selected transfer models to answer to those questions. We found that existing transfer models highlighted key roles played by different actors involved and the importance of contextual factors in transfer processes. These transfer models lead to failure or success either in the same or in different settings. However, we realized that these transfer models ignore taking into account interactions which exist in transfer processes as well as the evolution of key actors and changes in contextual factors. There is a need to create new models for efficient transfer of managerial practices in health systems. We propose to develop, test, and discuss new transfer models that consider changes in transfer process and where interactions are highlighted in the perspective of performance improvement.